2017
DOI: 10.1002/adsc.201700427
|View full text |Cite
|
Sign up to set email alerts
|

Photopromoted Entry to Benzothiophenes, Benzoselenophenes, 3H‐Indoles, Isocoumarins, Benzosultams, and (Thio)flavones by Gold‐Catalyzed Arylative Heterocyclization of Alkynes

Abstract: Visible light-promoted and gold-photoredox catalyzed reactions of heteroatom(N, S, Se, O)-tethered alkynes with arenediazonium salts selectively reacted to build vicinal diaryl-substituted 2H-benzo[e][1,2]thiazine 1,1-dioxides (benzosultams), benzoselenophenes, benzothiophenes, 4H-chromen-4-ones (flavones), 3H-indoles, 1H-isochromen-1-ones (isocoumarins), and 4H-thiochromen-4-ones (thioflavones). Moreover, the utility of functionalized 3H-indoles as precursors for further elaboration has been demonstrated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 69 publications
1
42
0
Order By: Relevance
“…In particular, Au‐catalyzed transformations that make use of light in combination with diazonium salts have been identified . In these transformations diazonium salts commonly serve as aryl donors, leading to the extrusion of N 2 (for representative examples see Scheme A) . In 2016 the group of Fensterbank reported the synthesis of arylated benzofurans from o ‐alkynylphenols combining a photo(redox) catalyst (Ru(bpy) 3 (PF 6 ) 2 ) and a Au catalyst .…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…In particular, Au‐catalyzed transformations that make use of light in combination with diazonium salts have been identified . In these transformations diazonium salts commonly serve as aryl donors, leading to the extrusion of N 2 (for representative examples see Scheme A) . In 2016 the group of Fensterbank reported the synthesis of arylated benzofurans from o ‐alkynylphenols combining a photo(redox) catalyst (Ru(bpy) 3 (PF 6 ) 2 ) and a Au catalyst .…”
Section: Methodssupporting
confidence: 56%
“…The previously proposed mechanism by Fensterbank and co‐workers employing a photo(redox) catalyst proposes a photochemical oxidative addition of the diazonium salt to the Au I complex producing a highly Lewis acidic Au III intermediate, that provides an open coordination site able to function as a π‐acid. Here, as in many other studies, a vinyl Au III intermediate is proposed to then form upon reaction with an o ‐alkynylphenol substrate and reductive elimination results in the formation of the arylated benzofuran products. Stoichiometric experiments have indeed demonstrated that the photochemical oxidative addition of diazonium salts is feasible both in an inter‐ and intramolecular fashion .…”
Section: Methodsmentioning
confidence: 98%
“…Fouquet et al and Gauchot and Scheme51. Dual Au and photoredox catalyzedbis-arylative C(sp)ÀC(sp 2 ) bond-forming cross-coupling reactionsi nvestigated by (a-e) Alcaide et al [269,270] and (f) Wang et al [271] Scheme53. Dual Au and photoredox catalyzedbis-arylative C(sp)ÀC(sp 2 ) bond-forming cross-coupling reactionsi nvestigated by (a-e) Alcaide et al [269,270] and (f) Wang et al [271] Scheme53.…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
“…Dual Au and photoredox catalyzedC ÀCcross-coupling of alkynes with aryl diazonium salts throughanarylative version of the Meyer-Schuster rearrangement, studied by (a) Gloriuse tal., [266] (b) Alcaide et al, [267] and (c) Shin et al [268] Scheme52. Dual Au and photoredox catalyzedbis-arylative C(sp)ÀC(sp 2 ) bond-forming cross-coupling reactionsi nvestigated by (a-e) Alcaide et al [269,270] and (f) Wang et al [271] Scheme53. Dual Au and photoredox catalyzedintramolecular( a) alkoxyarylation, [272] (b) amino-arylation, [273] and (c) ipso-arylation-cyclization [274] reactions of alkynes with aryl diazonium salts.…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
“…To determine the feasibility of using ynones as precursors, 1‐[2‐(methylthio)phenyl]‐3‐phenylprop‐2‐yn‐1‐one ( 2 a ) was treated with 2‐(2‐fluoropyridinium‐1‐yl)‐1,1‐bis[(trifluoromethyl)sulfonyl]ethan‐1‐ide ( 1 ) in acetonitrile at room temperature. Interestingly, the formation of bis(triflyl)thioflavone ( 3 a ) was observed (Scheme ) rather than Friedel–Crafts‐type bis(triflyl)alkylation or cyclobutene construction (Scheme ).…”
Section: Resultsmentioning
confidence: 99%